Problems and prospects of digitization and the use of artificial intelligence in medicine - Kharytonov, Evgen; Kharytonova, Olena; Tkalych, Maxym; Tolmachevska, Yuliia (DIXI, 2026)
This article examines the key trends, challenges, and prospects of digital transformation and the implementation of artificial intelligence (AI) in the field of medicine. With the advent of the fourth industrial revolution and the transition to a post-industrial economy, digital technologies and AI have significantly penetrated healthcare, changing the landscape of diagnostics, treatment, and administrative functions. The study explores the benefits of AI, including personalized treatment, accelerated diagnostics, and more efficient resource management. Simultaneously, it emphasizes the risks — ethical, legal, and data security concerns — which complicate the responsible integration of these technologies. Special attention is given to Ukraine’s efforts in implementing eHealth reforms, expanding telemedicine, and incorporating AI in clinical practice during the ongoing war. International and domestic experiences are analyzed to assess the applicability and consequences of AI solutions in healthcare. The article concludes by underlining the urgent need for comprehensive legal frameworks, ethical standards, and data protection mechanisms to maximize AI’s potential in medicine while minimizing threats to human rights and safety.